2012
DOI: 10.1177/1359105311435428
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and positive affect are associated with subjective health in women of the general population

Abstract: Poor subjective health has been associated with higher levels of inflammatory cytokines. We investigated whether such an association would apply to women of the general population. Levels of cytokines, affect and subjective health were assessed in 347 women of the general population aged 45 to 90 years. Higher levels of interleukin-6 were associated with poor subjective health, especially in participants over 65 years of age. Positive affect was a more robust determinant of subjective health than negative affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 39 publications
8
36
2
Order By: Relevance
“…These findings agree with those from cross-sectional studies linking SRH and low-grade systemic inflammation (e.g., Andreasson et al, 2013; Janszky et al, 2005; Lekander et al, 2004; Nakata, Takahashi, Otsuka, & Swanson, 2010). However, the present study extends these previous findings by demonstrating that the between-subject association was similar across up to 10 assessments over five years, which lends further weight to the link between SRH and inflammation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings agree with those from cross-sectional studies linking SRH and low-grade systemic inflammation (e.g., Andreasson et al, 2013; Janszky et al, 2005; Lekander et al, 2004; Nakata, Takahashi, Otsuka, & Swanson, 2010). However, the present study extends these previous findings by demonstrating that the between-subject association was similar across up to 10 assessments over five years, which lends further weight to the link between SRH and inflammation.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, cross-sectional associations can be driven by either stable or momentary relationships; this study indicates that such associations are due primarily to stable relationships. In addition, it adds evidence to the conclusion that the previously demonstrated relationship between SRH and inflammation in patient populations (Lekander et al, 2004; Janszky et al, 2005) and representative population samples (Andreasson et al, 2013) is not an artifact of poor control over disease or medication, since such relations should likely be captured by the medium time scale changes analyses presented in the current study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the presence of low-grade inflammation may be an important determinant of individuals' subjective health. For example, a recent study from primary health care in Stockholm revealed that inflammatory cytokines were associated with poor subjective health, especially in participants over 65 years of age (Andreasson et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In non-pregnant adults, several studies have examined associations between self-rated health and inflammation (1219). For example, a study of 1,727 community-dwelling elderly adults found a graded association between a single-item measure of self-rated health and IL-6 (12).…”
Section: Introductionmentioning
confidence: 99%